Optimalisasi Konten Sosial Media dan Artikel Seo untuk Meningkatkan Brand Awareness dan Konversi Penjualan UMKM Rumah Kapas - Visi Ari Pratiwi; Acep Samsudin (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
In the digital era, Micro, Small, and Medium Enterprises (MSMEs) face various challenges and opportunities. Social media and Search Engine Optimization (SEO) are promising solutions to increase brand awareness and sales conversions. This study aims to determine the effectiveness of implementing social media and SEO article optimization on the brand awareness and sales conversions of Rumah Kapas MSME. The results showed that optimizing Instagram and Tiktok social media content, as well as SEO articles, successfully increased the brand awareness and sales conversions of Rumah Kapas MSME. This is evidenced by the increase in the number of followers, reach, and engagement on social media, as well as website traffic and sales.